Ntaganda Case: Lessons learnt from Katanga, Lubanga, and Bemba Cases = Caso Ntaganda : Lições extraídas dos casos Katanga, Lubanga e Bemba - Amaral, Ana Silvia Sanches (Revista Eletrônica de Direito Penal e Política Criminal, 2023)
The Prosecutor v. Bosco Ntaganda was the first case in which the International Criminal Court (ICC) issued a conviction on sexual and gender-based crimes (SGBCs). However, Ntaganda´s condemnation for rape and sexual slavery came as the crowning point of a lengthy process of development of the Court´s approach to the prosecution of sexual and gender crimes, along three cases- Thomas Lubanga Dyilo, Germain Katanga e Jean-Pierre Bemba Gombo.The present work analyses the impact of each of the cases in the International Criminal Court handling of sexual and gender-based crimes and how they paved the way for punishmenr of Ntaganda for the crimes of rape and sexual slavery.